Liver transplantation for progressive familial intrahepatic cholestasis: Clinical and histopathological findings, outcome and impact on growth - Aydogdu, Sema; Cakir, Murat; Arikan, C.; Tumgor, Gokhan; Yuksekkaya, Hasan Ali; Yilmaz, Funda; Kilic, Murat (Pediatric transplantation, 2007)
:  In this study, we analyze the demographic features, clinical and histopathological findings in patients who underwent liver transplantation for progressive familial intrahepatic cholestasis. We also analyze outcome and impact of liver transplantation on growth and bone mineral content. Most of the patients were presented with jaundice mainly beginning within the first six months. At the time of initial admission; eight patients had short stature (height SD score <2), and four patients had weight SD score <2. Liver transplantation were performed at the age of 43.2 ± 27 months (range 9 to 96 mfonths), 6.5 ± 3.5 months later after the first admission. Infection, surgical complications and osmotic diarrhea associated with severe metabolic acidosis were noted in 41.4%, 16.6% and 33.3%, respectively. One patient developed posttransplant lymphoproliferative disorder. Overall; 1 year graft and patient survival was 69.2% and 75%, respectively. At the end of the 1st year only 2 patients had height SD score <2. Linear regression of height gain against increase in total body BMD measured at the time of transplantation and 1 year after liver transplantation gave a coefficient r = 0.588 (p = 0.074). No correlation was found between the height gain and age and PELD score at time of transplantation, and no difference was noted between the sexes and donor type. Liver transplantation is effective treatment modality with good outcome and little morbidity, and increases the growth acceleration in patients with PFIC associated with cirrhosis.